Dynamic programming and Munkres algorithm for optimal photovoltaic arrays reconfiguration - Sanseverino, Eleonora Riva; Ngoc, Thanh Ngo; Cardinale, Marzia; Li Vigni, Vincenzo; Musso, Domenico; Romano, Pietro; Viola, Fabio (Solar energy, 2015)
[Display omitted] •Optimal design for PV plant.•Switching matrix design.•Switching operations balancing.•Comparison between reconfiguration algorithms. In this paper, an original formulation of the control problem for optimal PV array reconfiguration, following a Total Cross Tied layout, is proposed. The formulation follows the well-known subset sum problem, which is a special case of the knapsack problem. The reconfiguration is a measure devoted to mitigate the mismatch effect and maximize the output power of small photovoltaic plants under non-homogeneous working conditions. Therefore, reconfiguration means changing the connections of the solar panels adaptively by a dynamic switching matrix. The control system implements an easy dynamic programming algorithm to change the switches layout. The use of the Munkres assignment method in a post-processing module makes the algorithm able to obtain the optimum configuration for which it is possible to balance and minimize the aging of the switches within the switching matrix.